Noninvasive Cervical Vagal Nerve Stimulation Alters Brain Activity During Traumatic Stress in Individuals With Posttraumatic Stress Disorder. Issue 9 (21st November 2021) - Wittbrodt, Matthew T.; Gurel, Nil Z.; Nye, Jonathon A.; Shandhi, Md Mobashir H.; Gazi, Asim H.; Shah, Amit J.; Pearce, Bradley D.; Murrah, Nancy; Ko, Yi-An; Shallenberger, Lucy H.; Vaccarino, Viola; Inan, Omer T.; et al.
Abstract : Supplemental digital content is available in the text. ABSTRACT: Objective: Posttraumatic stress disorder (PTSD) is a disabling condition affecting a large segment of the population; however, current treatment options have limitations. New interventions that target the neurobiological alterations underlying symptoms of PTSD could be highly beneficial. Transcutaneous cervical (neck) vagal nerve stimulation (tcVNS) has the potential to represent such an intervention. The goal of this study was to determine the effects of tcVNS on neural responses to reminders of traumatic stress in PTSD. Methods: Twenty-two participants were randomized to receive either sham ( n = 11) or active ( n = 11) tcVNS stimulation in conjunction with exposure to neutral and personalized traumatic stress scripts with high-resolution positron emission tomography scanning with radiolabeled water for brain blood flow measurements. Results: Compared with sham, tcVNS increased brain activations during trauma scripts ( p < .005) within the bilateral frontal and temporal lobes, left hippocampus, posterior cingulate, and anterior cingulate (dorsal and pregenual), and right postcentral gyrus. Greater deactivations ( p < .005) with tcVNS were observed within the bilateral frontal and parietal lobes and left thalamus. Compared with tcVNS, sham elicited greater activations ( p < .005) in the bilateral frontal lobe, left precentral gyrus, precuneus, and thalamus, and right temporal and parietal lobes, hippocampus, insula, and posterior cingulate. Greater ( p < .005) deactivations were observed with sham in the right temporal lobe, posterior cingulate, hippocampus, left anterior cingulate, and bilateral cerebellum. Conclusions: tcVNS increased anterior cingulate and hippocampus activation during trauma scripts, potentially indicating a reversal of neurobiological changes with PTSD consistent with improved autonomic control. Trial Registration: No. NCT02992899.